The WNT/β-catenin signaling inhibitor XAV939 enhances the elimination of LNCaP and PC-3 prostate cancer cells by prostate cancer patient lymphocytes in vitro - Stakheev, Dmitry; Taborska, Pavla; Strizova, Zuzana; Podrazil, Michal; Bartunkova, Jirina; Smrz, Daniel (Scientific reports, 2019)
Upregulated Wnt/β-catenin signaling is associated with increased cancer cell resistance and cancer cell-elicited immunosuppression. In non-neoplastic immune cells, upregulated Wnt/β-catenin is, however, associated with either immunosuppression or immunostimulation. Therefore, it is difficult to predict the therapeutic impact inhibitors of Wnt/β-catenin signaling will have when combined with cancer immunotherapy. Here, we evaluated the benefit(s) of the Wnt/β-catenin signaling inhibitor XAV939 in the in vitro elimination of LNCaP prostate cancer cells when cocultured with lymphocytes from patients with localized biochemically recurrent prostate cancer (BRPCa). We found that 5 µM XAV939 inhibited β-catenin translocation to the nucleus in LNCaP cells and CD4+ BRPCa lymphocytes without affecting their proliferation and viability. Preconditioning BRPCa lymphocytes with 5 µM XAV939 accelerated the elimination of LNCaP cells during the coculturing. However, during subsequent re-coculturing with fresh LNCaP cells, BRPCa lymphocytes were no longer able to eliminate LNCaP cells unless coculturing and re-coculturing were performed in the presence of 5 µM XAV939. Comparable results were obtained for PC-3 prostate cancer cells. These findings provide a rationale for combining cell-based immunotherapy of PCa with inhibitors of Wnt/β-catenin signaling.
Keywords: Tankyrases; beta-katenin; heterocyklické sloučeniny tricyklické; tankyrasy; Cell Line, Tumor; proteiny Wnt; Immunotherapy; lidé; Antineoplastic Agents; protinádorové látky; nádory prostaty; buňky PC-3; T-lymfocyty; Prostatic Neoplasms; Wnt Signaling Pathway; Heterocyclic Compounds, 3-Ring; Humans; Male; imunoterapie; Aged; Wnt Proteins; signální dráha Wnt; lidé středního věku; CD4-Positive T-Lymphocytes; senioři; mužské pohlaví; PC-3 Cells; T-Lymphocytes; beta Catenin; Middle Aged; nádorové buněčné linie; CD4-pozitivní T-lymfocyty